Microbial Profiling of Saliva, Oral Rinse, Subgingival Plaque and GCF Reveals Site‐Specific Dysbiosis in Periodontitis: A Within‐Subject Comparison of 150 Participants - Lee, Ran; Park, Jin‐Young; Park, Yuan; Kim, Kyu; Ha, Jong‐Won; Lee, Jung‐Seok (Journal of clinical periodontology, 2025)
This study aimed to compare the microbial communities across four oral sample types-saliva, oral rinse, subgingival plaque and gingival crevicular fluid (GCF)-and to identify disease-associated microbiota in periodontitis. Oral samples were collected from 150 adults, each providing four types of samples in the same visit. Saliva (5 mL) and oral rinse (10 mL, 30-s swish) were collected prior to clinical examination. Subgingival plaque was sampled using a curette from the two deepest pockets, followed by GCF collection via 20-s insertion of gingival retraction cords at the same sites. All samples underwent 16S rRNA (V3-V4) sequencing. Site-specific microbial profiles were evaluated across all participants. For disease comparisons, only individuals with clear periodontal status (periodontally healthy, n = 41; stage III/IV periodontitis, n = 43) were included, excluding stage I/II cases (n = 66). Saliva and oral rinse formed one microbial cluster; plaque and GCF formed another. Alpha diversity was found increased in disease, except in GCF. Beta diversity showed the most distinct disease-related shift in GCF. Red complex pathogens and GCF-specific differentially abundant taxa were markedly enriched in periodontitis. GCF yielded the clearest microbial differentiation between health and periodontitis, supporting its diagnostic utility.